PERANAN DIDIKAN SUBUH DALAM MEMBANGUN MENTAL PUBLIC SPEAKING SANTRI TPA MASJID RAYA LIMA KAUM - Rismania (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2025)
This research aims to find out the role of dawn education in developing the mental public speaking of Santri TPA Masjid Raya Lima Kaum. This research aims to identify the extent to which dawn education contributes to the formation of mental public speaking among the students of TPA Masjid Raya Lima Kaum. Through participatory observation and in-depth interviews, it was found that routine activities in dawn education, such as memorizing the Koran, giving speeches and group discussions, gradually trained students to have the courage to speak in public. The process of internalizing Islamic values in a conducive environment also has a positive correlation with increasing students' self-confidence in expressing opinions. The results of this research show that dawn education is not just religious learning, but also becomes a forum for students to develop soft skills that are relevant to the demands of the times